2021
DOI: 10.1111/ppc.12908
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between nursing students’ professional attitudes and caring behaviors: A cross‐sectional study

Abstract: Purpose This study aimed to determine the relationship between nursing students' professional attitudes and caring behaviors. Design and Methods The research is a cross‐sectional, descriptive, and correlational study. The study was conducted with 202 nursing students. The participation rate was 95%. Findings The total Instrument of Professional Attitude for Student Nurses mean score was 106.708 ± 20.24 and the Caring Behaviors Inventory‐24 mean score of the nursing students was 5.23 ± 0.88. A positive weak cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…The importance of this study relies on the fact that it is the first study (up to the authors' knowledge) conducted to investigate this topic in the Middle East countries, more superficially among nursing students from six different countries. Hence, the findings might be unique and transferrable to other countries with similar cultural and moral characteristics; especially since the literature review revealed that most of the studies in this field were conducted in Western countries, such as the USA, the Netherlands and Cyprus (Kılıç & Ak, 2020 ; Nadelson et al, 2016 ; van Leeuwen & Jukema, 2018 ), and Turkey (Atar & Asti, 2020 ; Gunay & Ozdemir, 2020 ; Sümen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this study relies on the fact that it is the first study (up to the authors' knowledge) conducted to investigate this topic in the Middle East countries, more superficially among nursing students from six different countries. Hence, the findings might be unique and transferrable to other countries with similar cultural and moral characteristics; especially since the literature review revealed that most of the studies in this field were conducted in Western countries, such as the USA, the Netherlands and Cyprus (Kılıç & Ak, 2020 ; Nadelson et al, 2016 ; van Leeuwen & Jukema, 2018 ), and Turkey (Atar & Asti, 2020 ; Gunay & Ozdemir, 2020 ; Sümen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As for nursing students, college is an important stage in developing nursing professionalism. Students with higher nursing professionalism will be able to contribute more to a nursing career that is more stable and more professionally satisfying [ 2 , 3 , 4 , 5 ]. More theoretical and practical insights are needed in this area in the future to explore the professionalism of nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing professionalism refers to the systematic view of nursing as the value orientation and standards of practicing nurses, reflecting the cognitive, attitudinal, and psychomotor dimensions of nursing [ 1 ]. Nursing professionalism plays a positive role in enhancing satisfaction with the major of nursing and caring behavior by allowing nursing students to clearly set career goals [ 2 , 3 , 4 ]. In addition, it plays an important role in increasing nurses’ intention to work and improve their clinical performance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamızda öğrencilerin bakım davranış düzeyi toplam puan ortalaması iyi düzeyde bulunmuştur. Hemşirelik öğrencileri ile gerçekleştirilen, ülkemizdeki (Sümen et al, 2021;Türk ve ark., 2018;Birimoğlu ve Ayaz, 2015;Dığın ve Özkan, 2020) ve yurtdışındaki (Labrague et al, 2017) çalışmalarda da öğrencilerin bakım algısı yüksek bulunmuştur. Ölçekten alınan puan arttıkça, öğrencilerin bakım davranışları algısının iyi olduğunu ve geleceğin hemşireleri olan öğrenci hemşirelerde bakım davranış düzeylerinin yüksek olduğunu söylemek mümkündür.…”
Section: Discussionunclassified
“…Bu sonuç, kaliteli bakım ve hasta memnuniyeti açısından önemlidir. Literatürde konuyla ilgili yapılan farklı çalışmalarda da (Türk ve ark., 2018, Sümen et al, 2021, Dığın ve Özkan, 2020, Labrague et al, 2017 çalışma bulgularımız ile benzer şekilde bağlılık alt boyutu puan ortalaması düşük bulunmuştur.…”
Section: Discussionunclassified